Numerical modelling of horizontal axis tidal turbine with variable length blade / Farhana Arzu - Farhana, Arzu (2018)
Marine renewable energy is one of the major alternative sources of energy to meet the current energy demand. Rotor blades have the main influence on the efficiency of tidal turbines. The variable length blade technology has already been used in designing wind turbine blades for efficient energy extraction. The movable tip blade section of variable blade length turbine offers full control on performance characteristics and power capture, but has limited application in marine field. In this study, a variable length blade horizontal axis tidal turbine (HATT) model is studied numerically to investigate the hydrodynamic performance and power output. A new open source software package QBlade 0.8 and ANSYS FLUENT 15.0 were used for two-dimensional BEMT (blade element momentum theory) and three-dimensional CFD (computational fluid dynamics) simulations respectively. Both the simulation techniques have been validated against the available published data of the HATT models. The effect of different tip blade extensions on the non-dimensional performance parameters (power, thrust and moment coefficient) and power output of the rotor model were studied at rated and below-rated conditions of the model. The performance data then were compared with the standard fixed length blade tidal turbine. Non-dimensional performance coefficients were observed to improve with the increment of rotor diameter at high TSRs. Peak power coefficient value was dropped by 9% when the blades extend from 10% to 40%. On the other hand, power extraction was enhanced up to 72% at below-rated tidal velocities without any loss in performance at rated condition. The model is found to be more efficient compared with the conventional tidal turbine models and thus recommended as a good candidate to replace the other conventional HATTs.